PENINGKATAN KOMPETENSI GURU MELALUI KEGIATAN MELUKIS MENGGUNAKAN MEDIA BERBASIS KEARIFAN LOKAL DI KECAMATAN SEMARANG BARAT - Ismatul - Khasanah (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Art education in kindergarten is part of the process of forming a whole individual in accordance with the goals of national education. Art education includes dance, music, visuals and drama. This activity aims to provide assistance to kindergarten / early childhood teachers in artistic creativity and creativity, especially painting activities using local wisdom-based media so that they can be applied in teaching and learning activities in kindergarten / early childhood education. As for art and reativity, what is meant is not only to form skilled students at imagination through fine arts, but also to form appreciative and creative personalities through the experience of art processing. This activity can contribute not only to the development of teaching materials, but also to the ability of kindergarten / early childhood teachers to create art, especially art and creativity which can have a positive effect on the development of teacher skills by packaging teaching materials based on art and creativity according to the needs of garden children childhood and early childhood education. This PKM activity was attended by Kindergarten / Early Childhood Teachers who are members of the entire West Semarang District, Semarang City.